Seat belt syndrome: a case report - Nigam, Vinod Kumar; Nigam, Sidharth (International Surgery Journal, 2021)
Seat belt syndrome happens when a car meets an accident and person sitting in the car with seat belt on gets abdominal injuries typically, seat belt mark with intestinal injuries and factures of ribs and lumber spine. The abdominal injuries are usually intestinal perforations. Doctor seeing the motor vehicle accident must keep in mind seat belt syndrome while examining. As the traffic rules are getting enforced strictly in developing countries we are seeing seat belt syndrome cases in these countries more and more. We presented here a case of seat belt syndrome in 35 years old women.